ANALISIS PELAKSANAAN PROGRAM KEMITRAAN DALAM RANGKA PEMBERDAYAAN UKM (Studi Kasus Program Kemitraan PT TELKOM Cabang Palu Sulawesi Tengah) - Fitria, Ria; Jurana, Jurana (BISNIS, 2015)
This research aims to know the system and the procedure for the implementation  of  the partnership  program  and  its  influence  on the quality of the SMBS become partner PT Telkom. This laboratory of the adoption by the exportation of cases the implementation of the partnership program which occurs on PT Telkom. The results of this research can be used as a reference for students, faculty and researchers who wish to develop further research. In addition, this research is also useful as early studies to evaluate the implementation of the partnership program which is in PT Telkom Branches Palu.The research method used is the method of descriptive analysis based on the case study, namely approach which compare the conceptual characteristics, SOP system and folow-up procedures partnership program on PT Telkom compared with empiric phenomenon that occurs on PT Telkom Branches Palu. The sources of the data obtained through several ways by observation, interview, study document and  the questioner from the secondary data. Through the evaluation that has been done, the authors conclude that there is a discrepancy in some of the things in the implementation of the company operational standards (SOP) partnership program on  CDC Unit PT Telkom Branches Palu, and not decide the implementation of internal control especially CDC unit that causes the implementation and the achievement of the purpose of the partnership program has not been achieved. Based on the results of research can be recommended to PT Telkom for more maximize the construction process such as training or business consulting periodically. In addition, increase the number of  CDC Unit staff to maximize performance. While, suggestions for SMBS expected to make financial reports regularly and actual.